2016
DOI: 10.1111/jen.12298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of host plants on the infectivity of nucleopolyhedrovirus to Spodoptera exigua larvae

Abstract: Previous studies have shown that the infectivity of baculovirus to herbivores is affected by phytochemicals ingested during the acquisition of viral inoculum on the foliage of host plants. Here, we measured the effects of 14 host plant species on the infectivity of Spodoptera exigua nucleopolyhedrovirus (SeNPV) to its larvae. The order of the LD 50 values of SeNPV among the host plants was Ipomoea aquatica > Brassica oleracea > Raphanus sativus > Amaranthus tricolor > Spinacia oleracea > Vigna unguiculata > So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 29 publications
0
28
0
5
Order By: Relevance
“…Spodoptera exigua multiple nucleopolyhedrovirus ('NPV' hereafter) is an important biocontrol agent of beet armyworm, and is able to cause epizootics in populations of this herbivore . In an earlier study, we measured the effects of 14 species of host plants on the susceptibility of beet armyworm to NPV, and found high susceptibility of caterpillars raised on a diet of soybeans ( Glycine max ), intermediate susceptibility of those fed collards ( Brassica oleracea ) and low susceptibility of those fed water convolvuluses ( Ipomoea aquatica ) . In the current study, we used these three plants together with an artificial diet to examine the mechanisms underlying viral effects on the immune response of beet armyworm to NPV.…”
Section: Introductionmentioning
confidence: 99%
“…Spodoptera exigua multiple nucleopolyhedrovirus ('NPV' hereafter) is an important biocontrol agent of beet armyworm, and is able to cause epizootics in populations of this herbivore . In an earlier study, we measured the effects of 14 species of host plants on the susceptibility of beet armyworm to NPV, and found high susceptibility of caterpillars raised on a diet of soybeans ( Glycine max ), intermediate susceptibility of those fed collards ( Brassica oleracea ) and low susceptibility of those fed water convolvuluses ( Ipomoea aquatica ) . In the current study, we used these three plants together with an artificial diet to examine the mechanisms underlying viral effects on the immune response of beet armyworm to NPV.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported effects of plant species on the susceptibility of several insects to their entomoviruses, including that of Helicoverpa zea (Ali et al., , ; Farrar & Ridgway, ; Forschler, Young, & Felton, ) and Heliothis virescens (Ali et al., , ; Hoover et al., ). Some cases found higher mortality (Forschler et al., ), shorter mean time to death (Ali et al., ), lower LD 50 (Ali et al., ) and shorter LT 50 (Wan et al., ) after virus‐infected larvae of noctuids fed on soybeans. But these same four susceptibility indices showed the opposite trend when virus‐infected larvae were fed on collards (Farrar & Ridgway, ; Shikano et al., ; Wan et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…(Ali et al., ; Farrar & Ridgway, ; Shikano et al., ; Wan et al., ), while it is higher on oligophenolic plants (soybeans, corns, tomatoes, etc.) (Ali et al., ; Forschler et al., ; Monobrullah et al., ; Wan et al., ). Phenolics from the foliage can inhibit the infectivity of the entomovirus to tissues in insect guts, thus decreasing the susceptibility of larvae to the entomovirus (Ali et al., ; Felton, Duffey, Vail, Kaya, & Manning, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations